M-RSF: a multilevel feedback queue task scheduling mechanism for Unikernel - DONG Bonan; YANG Qiusong; LI Mingshu (Tongxin xuebao)
Unikernel, as a cutting-edge technology in the field of cloud computing, is characterized by its fast start-up speed and minimal resource usage. However, in the context of large-scale task scheduling in cloud environments, Unikernel currently lacks a customized scheduling mechanism based on its task characteristics, which hinders the further exploitation of its performance advantages. To address this issue, the distinctive task characteristics of Unikernel were initially summarized. Subsequently, a novel multi-level feedback queue scheduling mechanism for Unikernel, referred to as M-RSF, along with its mathematical model, were proposed. Without affecting the structural features of Unikernel, this mechanism could more effectively schedule Unikernel tasks in cloud environments. Meanwhile, a new load model was put forward based on an in-depth analysis of task characteristics. The model not only accurately depicted the task characteristics of Unikernel but also provided a more reasonable value setting for the scheduling policy parameters in M-RSF. Lastly, the implementation and validation of the M-RSF scheduling mechanism on the OSv Unikernel were conducted. Experimental results indicate that M-RSF can effectively reduce the average waiting time and average turnaround time of the OSv Unikernel during large-scale task scheduling, achieving a reduction of more than 15% compared to the unmodified OSv Unikernel.